Perancangan Ulang Tata Letak pada Galangan Kapal Tradisional menggunakan Blocplan-90 - Heri Tri Irawan; Bismi Khairijal; Iing Pamungkas; T.M. Azis Pandria; Arhami Arhami; Hasnita Hasnita; Risnadi Irawan (Universitas Teuku Umar, 2023)
CV. Rasya Jaya is a traditional fishing boat manufacturing company located in Padang Seurahet, Kec. Johan Pahlawan, Aceh Barat Regency. The facility layout of CV. Rasya Jaya has several workstations that are not in the correct location for the production process or the relationship between related rooms. This results in inefficient and ineffective material handling, as well as reduced worker comfort. The poorly organized facilities also contribute to production constraints. Therefore, it is necessary to evaluate the production facility layout at CV. Rasya Jaya. The goal is to provide an alternative design for the production facility layout that is more efficient and effective in terms of the relationship between the production process flow and minimizing material flow in the production process. The purpose of this study is to determine the optimal layout at CV. Rasya Jaya using the Blocplan algorithm. Blocplan-90 is an algorithm for solving spatial layout problems that can handle both quantitative and qualitative data. Mathematical models within the design are developed with computer applications for models that work with the limitations of workstation shapes. Based on the results of the layout design of facilities at CV. Rasya Jaya, three main layouts were created: office layout, facility layout, and production layout. The total area of the three layouts is 1739 m2.